Perspectives of pain in patients with type 2 diabetes. Issue 3 (4th May 2019) - Kirk, Julienne K; Hunter, Jaimie C; Mihalko, Shannon L; Danhauer, Suzanne C; Shumaker, Sally A
ABSTRACT: Introduction : Reducing symptom burden is often secondary to risk factor control in diabetes. Symptom burden with comorbid medical conditions and the need for symptom palliation are not well defined. Although neuropathy is one of the most frequent occurring comorbidities of diabetes, patient experience is inconsistent. Using in-depth interview, we assessed patients' perspectives of pain experienced through neuropathy and the impact on type 2 diabetes management. Areas covered : Participants completed a structured telephone interview during which perspectives on diabetes and its management occurred. Data were analyzed iteratively using content analysis and extracted themes came from reduced data. Interview data were triangulated with clinical data from electronic health records. Expert opinion : During interviews, 41% of patients reported pain interfered with their lives. Three pain-related themes emerged from interviews, augmented by descriptions of how people experience and cope with pain. Themes included: (1) people know what neuropathy is and attribute their pain to it; (2) neuropathic pain seems insurmountable at times; and (3) pain can lead to feeling down or hopeless. Pain, a common comorbidity in diabetes, is a primary driver of patient suffering. Understanding how patients experience pain paves the way for creative interventions to manage it better among those living with diabetes.